13feet is larger as 4 yard is equivalent to 12 feet
Answer:
02:3 and 12:18
Step-by-step explanation:
A proportion is formed when the larger ratio can be simplified to equal the smaller ratio:
#1
02:3 and 4:12
Reducing the larger ratio: 4:12=1:3
Hence, not a proportion.
#2
02:3 and 6:12
Reducing the larger ratio: 6:12=1:2
Hence, not a proportion.
#3
02:3 and 12:18
Reducing the larger ratio: 12:18=2:3
Hence, they form a proportion.
#4
02:3 and 12:18
Reducing the larger ratio: 12:36=1:3
Hence, not a proportion.
Answer:
Step-by-step explanation:
Let's see if we can think of two numbers that multiply to be 3(-5)=-15
andd add up to be -2
How about -5 and 3? That work's! :)
Factor by grouping!
Step-by-step explanation:
it's an equilateral triangle so all sides are equal
using Pythagorean theorem
2(√6) raised to the power of 2 = √6 raised to the power of 2 + x raised to the power of 2
2(√6) raised to the power of 2 is 12
√6 raised to the power of 2 is 6
therefore 12=6 + x
x = 12-6
x=6
Step-by-step explanation:
(a) ∫₋ₒₒ°° f(x) dx
We can split this into three integrals:
= ∫₋ₒₒ⁻¹ f(x) dx + ∫₋₁¹ f(x) dx + ∫₁°° f(x) dx
Since the function is even (symmetrical about the y-axis), we can further simplify this as:
= ∫₋₁¹ f(x) dx + 2 ∫₁°° f(x) dx
The first integral is finite, so it converges.
For the second integral, we can use comparison test.
g(x) = e^(-½ x) is greater than f(x) = e^(-½ x²) for all x greater than 1.
We can show that g(x) converges:
∫₁°° e^(-½ x) dx = -2 e^(-½ x) |₁°° = -2 e^(-∞) − -2 e^(-½) = 0 + 2e^(-½).
Therefore, the smaller function f(x) also converges.
(b) The width of the intervals is:
Δx = (3 − -3) / 6 = 1
Evaluating the function at the beginning and end of each interval:
f(-3) = e^(-9/2)
f(-2) = e^(-2)
f(-1) = e^(-1/2)
f(0) = 1
f(1) = e^(-1/2)
f(2) = e^(-2)
f(3) = e^(-9/2)
Apply Simpson's rule:
S = Δx/3 [f(-3) + 4f(-2) + 2f(-1) + 4f(0) + 2f(1) + 4f(2) + f(3)]
S ≈ 2.5103